Intersectoral Event Study Analysis on the Indonesia Stock Exchange Regarding the 2025 Replacement of the Minister of Finance of the Republic of Indonesia - Ade Ria Nirmala; Umi Rachmah Damayanti; Ratna Nuraini; Ibrahim Musa (Research in Accounting Journal (RAJ), 2026)
This study examines the reaction of the Indonesian capital market to the 2025 replacement of the Minister of Finance of the Republic of Indonesia using an event study approach. Market reaction is assessed through abnormal returns of sectoral indices listed on the Indonesia Stock Exchange (IDX) within an event window of 20 trading days before and 20 trading days after the announcement date. The Jakarta Composite Index (JCI) is employed as a proxy for market return, while sectoral index closing prices serve as the primary data source. The analysis includes normality testing, one-sample t-tests, paired-sample t-tests, and comparative analysis of Average Abnormal Returns (AAR) across sectors. The findings reveal the presence of significant abnormal returns on several trading days surrounding the event, indicating that the ministerial replacement conveyed value-relevant information that elicited investor responses. However, the paired-sample t-test results show no statistically significant difference in average abnormal returns between the pre-event and post-event periods, suggesting that the market reaction was temporary and rapidly absorbed. Sectoral analysis further demonstrates heterogeneous responses, with the Technology, Industrials, and Healthcare sectors exhibiting the highest sensitivity, while the Consumer Non-Cyclicals and Consumer Cyclicals sectors showed relatively defensive characteristics. These results provide evidence that political-economic events can generate short-term market reactions, although their impact varies across sectors. The findings support the Semi-Strong Form of the Efficient Market Hypothesis and Signaling Theory, highlighting that investors interpret and respond to political information differently depending on sector-specific characteristics.